Relationships between mixed features and borderline personality disorder in 2811 patients with major depressive episode. (12th June 2015) - Perugi, G.; Angst, J.; Azorin, J.‐M.; Bowden, C. L.; Caciagli, A.; Mosolov, S.; Vieta, E.; Young, A. H.; ,
Abstract : Objective: The study focused on the relationship between mixed depression and borderline personality disorder (BPD). Method: The sample comprised 2811 patients with a major depressive episode (MDE). Clinical characteristics were compared in patients with (BPD+) and without (BPD−) comorbid BPD and in BPD+ with (MXS+) and without (MXS−) mixed features according to DSM‐5 criteria. Results: A total of 187 patients (6.7%) met the criteria for BPD. A DSM‐IV‐TR diagnosis of bipolar disorder (BD) was significantly more frequent in patients with BPD+ than in patients with BPD. Patients with BPD+ were significantly younger and reported lower age at onset than BPD−. Patients with BPD+ also showed more hypomania/mania in first‐degree relatives in comparison with patients with BPD−, as well as more psychiatric comorbidity, mixed features, atypical features, suicide attempts, prior mood episodes and antidepressant‐induced hypo/manic switches. Mixed features according to DSM‐5 criteria were observed in 52 (27.8%) BPD+. In comparison with MXS−, MXS+ were significantly younger at age of onset and at prior mood episode and had experienced more mood episodes and hypo/manic switches with antidepressant treatments. Conclusion: Major depressive episode patients with comorbid BPD reported a high prevalence of mixed features and BD. The presence of DSM‐5 mixed features in MDE patients with BPD may be associated with complex course and reduced treatment response.